2007
DOI: 10.1002/adma.200602276
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of a Titanium Material by High‐Pressure Torsion Improves Pre‐Osteoblast Attachment

Abstract: Ultrafine surface features are commonly used to modulate the cellular activity of a variety of materials including ceramics, [1,2] composites, [3,4] nanofibers, [5,6] and polymers. [7,8] However, the main challenge for materials in contact with bone remains the development of a material with both favorable surface and bulk properties to modulate not only cell-substrate interactions but also to ensure the long-term stability of the implant. This challenge has motivated researchers to develop bulk nanostructured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 31 publications
6
91
1
Order By: Relevance
“…The latter includes biomedical applications [3], the development of corrosionresistant materials, high fatigue life materials, enhanced magnetic and thermoelectric properties, and improved hydrogen adsorption kinetics [2]. Recently, a great attention was paid on achieving high strength and high electroconductivity in Cu-based alloys [4][5][6], and it was claimed that such materials possess both characteristics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The latter includes biomedical applications [3], the development of corrosionresistant materials, high fatigue life materials, enhanced magnetic and thermoelectric properties, and improved hydrogen adsorption kinetics [2]. Recently, a great attention was paid on achieving high strength and high electroconductivity in Cu-based alloys [4][5][6], and it was claimed that such materials possess both characteristics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ceramic products have been clinically applied as biomaterials, and their advantages include high biocompatibility, in vivo stability, and superior mechanical characteristics compared to biomaterials such as synthetic polymers, resins, and metals [1][2][3][4][5][6][7][8][9][10][11][12][13]. Alumina ceramics are particularly effective as biomaterials owing to their high strength, resistance to wear, and smooth surface [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ref. [47], the natural oxide layer on HPT Ti samples was quite different from that on their CG counterparts in chemical bonding structures. XPS studies revealed that the HPT-processed substrates showed a weakening of the Ti bonding in the TiO 2 on HPT sample, which may lead to the faster dissolution rate of the oxide during the formation of TNT layers.…”
Section: The Influence Of Substrate Grain Size On the Tnt Morphologiesmentioning
confidence: 99%